Promosi terhadap Keputusan Pembelian Mobil Daihatsu Sigra (Productivity, 2020)
This study aims to determine the effect of promotion on the Daihatsu Sigra car purchase decision at PT. Astra Daihatsu Malalayang. This research method uses a quantitative research approach. This research was conducted on Daihatsu Sigra consumers with a sample of 93 respondents. The result of R between the two variables is 0.565, meaning the relationship between promotion and purchasing decisions is moderate. Then R square (determinant coefficient) of 31.9%. This shows that the decision to buy Daihatsu Sigra car at PT. Astra Daihatsu Malalayang, 31.9% was influenced by promotion, while the other 68.1% was determined by other factors not examined in this study. Then the influence is interpreted that the promotion is one factor that is sufficient to influence the decision of buying a Daihatsu Sigra car. In this case that the promotion carried out by PT. Astra Daihatsu Malalayang can satisfy consumers, because promotion is a way to introduce existing products at PT. Astra Daihatsu Malalayang especially Daihatsu Sigra cars.